Hans Jonas' Integrative Philosophy of Life as a Foothold for Integrative Bioethics - Jurić, Hrvoje, filozof (2011)
European approach to bioethical problems emphasizes, among others, a need for the widened and deepened consideration of the very notion of life, which should be taken in account when speaking about ethical dimensions of manipulation with the life at different levels. This tendency could be traced in the works of Fritz Jahr, Albert Schweitzer, Georg Picht, Klaus Michael Meyer-Abich and especially Hans Jonas (1903–1993). In that sense, we should take into consideration not only Jonas' ethics of responsibility, developed in the late phase of his life, but also his long-term research of Gnostic religion and thought, as well as his attempt to establish the philosophical biology as a new philosophy of the human, nature and life. Jonas developed the integrative philosophy of life in which centre stands ethically connotated philosophy of nature, based both on the results of contemporary natural sciences and theological speculations. It shows us clearly what pluriperspectivity and integrativity in bioethics actually mean, because it is far from any reductionism and tries to include different scientific and non-scientific perspectives, offering at the same time a platform for their dialogical mediation.
Projekt MZOS
Projekt MZOS
ENG